The experiences of HIV and AIDS orphans who are heads of households at Ga-mothapo, Limpopo Province, South Africa - Malema, R. N.; Mothiba, T. M. (My University, 2014)
The purpose of this study was to determine the experiences of the HIV and AIDS orphans who are heads of households at Ga-mothapo area in the Capricorn District, Limpopo Province. A qualitative, explorative, descriptive research was conducted to explore and describe the experiences of those HIV and AIDS orphans who are heads of households at Ga-mothapo area in the Capricorn District, Limpopo Province. Non-probability purposive sampling technique was used to include 12 participants who voluntarily participated in the unstructured one-to-one interview sessions until data saturation was reached. Data were analysed using the Tesch’s open coding qualitative data analysis method. Two themes namely: Living conditions and interpersonal relationship in the community emerged. The study recommended that the local churches have to identify and support these orphans who are head of households. The educators have to encourage these orphans to build their future by schooling up to tertiary level. The social workers should also assist the orphans to receive social grants and monitor how it is utilised.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:1 (June), 2014, pp. 58-67.
Keywords: HIV/AIDS orphans; Child headed families; AIDS (Disease) -- South Africa